SOFTWARE REQUIREMENTS FOR THE PERSPECTIVE FILBERT GENEPOOL (HAZELNUT) - S. G. Biganova; Yu. I. Sukhorukikh; E. K. Pchikhachev (Новые технологии, 2020)
The main program requirements for a promising gene pool of filbert (hazelnut) are presented. It must be resistant to low and high temperatures, moisture deficit in the summer, to the main pests, such as bud and hazelnut sawyer, nut weevils and grey rot. Plant bushes should have moderate growth of up to 3 m in height and diameter of the crown, uniform ripening of fruits within 85-90 %, a husk less than a nut, entry into marketable fruiting since 4-5 years of age.The target yield of the kernel is more than 810 kg/ha, the fruits of the selection category are of high quality (at least 45 points), the fat content is 60-70 %, protein is 12-18 %, and the shelf life is up to 2 years.The creation of new varieties is carried out on the basis of hybridization, clonal selection, mutagenesis, genetic engineering methods, pedigree and polyploidy. To evaluate individual and comprehensive indicators of fruit quality, models and sample volumes are presented, which, with an error of 5% and significance level α = 0.05, vary from 2 to 124 measurements. Preliminary allocation of a promising gene pool is proposed to be carried out on the basis of three-year long observations of species, and if it is not possible, by a single assessment of the quality of the fruits, followed by adjustment in their vegetative offspring at the test site.